Flow of charged particles in Pb-Pb and pp collisions at the LHC - Berkat,Mohamed (2024)
This thesis investigates the transition of Quantum Chromodynamic (QCD) matter to a strongly interacting Quark Gluon Plasma (QGP), where quarks and gluons become deconfined. The expansion of this plasma exhibits characteristics of an ideal relativistic hydrodynamics system, suggesting a behavior similar to that of a perfect fluid. Collective behavior, indicating a QGP phase, is studied through anisotropic flow coefficients. While small collision systems like pp were considered benchmarks, collective phenomena question this perception, suggesting the formation of a QGP in smaller systems. This thesis introduces a novel method to detect flow in those systems. This thesis presents results from the Event Plane Method, the Cumulant Method, and the new method we developed. This new method reveals the presence of flow and anti-flow in pp collisions, while the Event Plane Method and the Cumulant Method were used to reproduce results from the ALICE collaboration.
Keywords: Quark Gluon Plasma; QGP; Quantum Chromodynamic; QCD; flow coefficients; Event Plane; Cumulants; ALICE